Dividend Smoothing and Debt Ratings - Aivazian, Varouj A.; Booth, Laurence; Cleary, Sean (Journal of Financial and Quantitative Analysis, 2006)
Abstract We find that firms that regularly access public debt (bond) markets are more likely to pay a dividend and subsequently follow a dividend smoothing policy than firms that rely exclusively on private (bank) debt. In particular, firms with bond ratings follow a traditional Lintner (1956) style dividend smoothing policy, where the influence of the prior dividend payment is very strong and the current dividend is relatively insensitive to current earnings. In contrast, firms without bond ratings flow through more of their earnings as dividends and display very little dividend smoothing behavior. In effect, they seem to follow a residual dividend policy.